2023
DOI: 10.3390/su151813401
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain Technology and Related Security Risks: Towards a Seven-Layer Perspective and Taxonomy

Sepideh Mollajafari,
Kamal Bechkoum

Abstract: Blockchain technology can be a useful tool to address issues related to sustainability. From its initial foundation based on cryptocurrency to the development of smart contracts, blockchain technology promises significant business benefits for various industry sectors, including the potential to offer more trustworthy modes of governance, reducing the risks for environmental and economic crises. Notwithstanding its known benefits, and despite having some protective measures and security features, this emerging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Loss of Private Keys : In case of key loss the user of the system can not retrieve the password as there is no option for key recovery. Thus in this scenario, there is a big chance of losing control of user data 41 .…”
Section: Proposed System Modelmentioning
confidence: 99%
“…Loss of Private Keys : In case of key loss the user of the system can not retrieve the password as there is no option for key recovery. Thus in this scenario, there is a big chance of losing control of user data 41 .…”
Section: Proposed System Modelmentioning
confidence: 99%
“…Security concerns are growing as a result of the frequent attacks on popular exchanges. A hacker needs to acquire the majority of mining power to gain control of a network, a concept commonly referred to as the 51 percent assault (Mollajafari & Bechkoum, 2023). Further investigation of this topic is crucial due to the potential consequences it may present, as indicated by Orcutt (2019) Multi-factor authentication is necessary to safeguard blockchain systems from malicious attacks by performing several security checks.…”
Section: The Implication Of Blockchain Technology In the Financial In...mentioning
confidence: 99%
“…Figure 2 represents the different disciplines and applications of Blockchain technology. 31,[34][35][36][37][38][39] F I G U R E 1 An illustration of a Block with its components. 3 depicts all stages with certain defining attributes as follows.…”
Section: Blockchain Endpoint and Taxonomymentioning
confidence: 99%
“…In 2023, mainly four studies 4,37,43,44 were found on the taxonomy. Mollajafari and Bechkoum 37 examined security risks in all layers of blockchain systems, categorizing them to better understand and defend against vulnerabilities.…”
Section: Related Literaturementioning
confidence: 99%